2005
DOI: 10.4141/s02-069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conservation with conventional tillage for potato production in Atlantic Canada: crop productivity, soil physical properties and weed control

Abstract: R. 2005. Comparison of conservation with conventional tillage for potato production in Atlantic Canada: crop productivity, soil physical properties and weed control. Can. J. Soil Sci. 85: 453-461. Conservation tillage (CT) for potato crop land has been increasing in Atlantic Canada, but producers are concerned that fields managed in this way may be wet, slow to warm in spring, have increased debris at harvest, exhibit higher soil compaction and result in reduced yield. The objective of this study was to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 16 publications
4
27
1
Order By: Relevance
“…The proportion of total yield in the marketable size classes was also not affected by either tillage or cover crop treatments (data not shown). These results are consistent with previous experiments that have shown that potato is relatively insensitive to differences in the timing of tillage operations prior to planting (Carter and Sanderson 2001;Carter et al 2005;Liebman et al 1996). Although forage legumes and perennial grasses are often used in rotation with potato, most previous comparisons utilize these as rotation crops, i.e.…”
Section: Tuber Yieldsupporting
confidence: 93%
“…The proportion of total yield in the marketable size classes was also not affected by either tillage or cover crop treatments (data not shown). These results are consistent with previous experiments that have shown that potato is relatively insensitive to differences in the timing of tillage operations prior to planting (Carter and Sanderson 2001;Carter et al 2005;Liebman et al 1996). Although forage legumes and perennial grasses are often used in rotation with potato, most previous comparisons utilize these as rotation crops, i.e.…”
Section: Tuber Yieldsupporting
confidence: 93%
“…The cropping history (barley-red clover rotations) for each site over the last decade was similar. Information on agronomic (crop yield, crop residue, weeds, soil clods) and environmental (soil water and temperature) aspects of the study were given in Carter et al (2005).…”
Section: Experimental Sitementioning
confidence: 99%
“…Carter et al (2005) presented the crop yield, weed control, crop residue, and soil environmental aspects of the study. In the present study, the responses to tillage practice and use of glyphosate were determined from a range of soil organic fractions, microbial properties, and soil physical properties including soil structure.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study indicated that potato yield could be similar between tillage systems provided that the growing season was relatively long (Ekeberg and Riley 1996). In short-term studies on sandy loam soils on a range of sites in Prince Edward Island, replacement of the mouldboard with a chisel plough within the potato phase had no adverse effect on potato yield and quality in both 2-and 3-yr potato rotations Holmstrom et al 1999;Carter and Sanderson 2001;Carter et al 2005).…”
mentioning
confidence: 98%